Pengaruh Edukasi Perawatan Metode Kanguru Terhadap Tingkat Pengetahuan Ibu Dengan Bayi BBLR - Fitri Harahap, Rahmaini; Sari Sinaga, Elvina; Fitrinelda Silaban, Verawaty; Br Kaban, Fitriana; Feediia Mona Saragih, Elv.; Hanum, Parida (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Low Birth Weight (LBW) infants are a significant factor contributing to the Infant Mortality Rate (IMR) worldwide, especially in developing countries. This study aims to evaluate the impact of education on Kangaroo Mother Care (KMC) on the knowledge level of mothers with low birth weight (LBW) babies at RSUD Bengkalis. The research design uses a pre-experimental design with a one group pre-test and post-test design.The sample size in this study was 33 people. This study uses the Purposive Sampling technique. The data collection instrument used in this study employed primary data in the form of a questionnaire on mothers' knowledge of kangaroo care for low birth weight infants, consisting of 20 questions. The results show that before the education, the majority of respondents had low knowledge, whereas after the education, the mothers' knowledge significantly increased. The Wilcoxon test results with a p-value < 0.05 prove that education about PMK is effective in increasing mothers' knowledge. The research is expected to provide better knowledge about kangaroo care in improving the health of LBW infants and reducing neonatal mortality rates. This research supports the implementation of health education programs to enhance mothers' awareness and skills in caring for low birth weight infants.